Pertanggungjawaban Developer Dalam Kasus Wanprestasi Atas Perjanjian Jual Beli Properti Melalui Sistem KPR - Kaban, Divany Harbina Emzilena; Adam, Chelsea Kairadinda; Amalia, Firda; Putri, Prastiwi Pramudya; Putri, Tiara Frianita; S, Surahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The issue of breach of contract by developers in property sale and purchase transactions through the Mortgage Loan (KPR) scheme has become a significant concern in consumer protection in Indonesia. This research aims to analyze the legal responsibility of developers and the legal protection efforts for consumers who suffer losses due to breach of contract in property sales under KPR agreements. The research method used is normative legal research with a statutory and case study approach. Data collection techniques include literature review, analysis of legal documents, and empirical data from banking reports and relevant cases. The data were analyzed qualitatively by interpreting applicable legal provisions and reviewing their implementation in practice. The results show that in the tripartite legal relationship between developers, consumers, and banks, each party has rights and obligations based on the principle of freedom of contract. When a developer commits a breach of contract, consumers are entitled to legal protection as stipulated in Law Number 8 of 1999 on Consumer Protection and the Indonesian Civil Code. This protection includes the right to compensation, the right to accurate information, and access to dispute resolution mechanisms. Consistent law enforcement is essential to safeguard consumer rights in the KPR system.